2014
DOI: 10.1371/journal.pone.0087328
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effects of Ethanol and Its Metabolite Acetaldehyde, on First Trimester Human Placental Cell Turnover and Function

Abstract: Fetal alcohol spectrum disorder (FASD) describes developmental issues from high maternal alcohol intake, which commonly results in fetal growth restriction and long term morbidity. We aimed to investigate the effect of alcohol and acetaldehyde, on the first trimester placenta, the period essential for normal fetal organogenesis. Normal invasion and establishment of the placenta during this time are essential for sustaining fetal viability to term. We hypothesise that alcohol (ethanol) and acetaldehyde have det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 85 publications
1
27
0
1
Order By: Relevance
“…In accordance with previous studies, we have observed an increase in apoptosis markers after the ethanol exposure [9,36,39]. Our study has evidenced a strong correlation between ethanol dose and hormonal release in the supernatant culture medium Determination of hCG and IGF2 in placental tissue obtained from fetuses exposed or not to ethanol.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous studies, we have observed an increase in apoptosis markers after the ethanol exposure [9,36,39]. Our study has evidenced a strong correlation between ethanol dose and hormonal release in the supernatant culture medium Determination of hCG and IGF2 in placental tissue obtained from fetuses exposed or not to ethanol.…”
Section: Discussionsupporting
confidence: 92%
“…The consequences of prenatal ethanol exposure (PEE) observed in infants could be attributable, in part, to the damage exerted to the cells and, as consequence, this cell system losses partially its function [9]. For this reason, biomarkers that offer reliable information about the injury produced in the fetus are necessary [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Animal models of FASD have demonstrated detrimental effects of prenatal alcohol exposure on placental size, structure, and function, although the majority of studies have been conducted in vitro using cell cultures and/or tissue sections (Burd et al., ). Alcohol exposure has been associated with trophoblast cell death via apoptosis in human placenta‐derived cell cultures (Clave et al., ; Lui et al., ) and decreased placental size (Andersson et al., ; Hollstedt et al., ; Kaminski et al., ; Niemelä et al., ). In a rat model, Gundogan and colleagues () found an alcohol‐related decrease in placental thickness, with the greatest effects in the labyrinthine layer, as well as an increase in untransformed maternal vessels, which result in diminished placental blood flow and nutrient transfer to the fetus.…”
mentioning
confidence: 99%
“…Studies have shown that alcohol alters the growth and function of the placenta (Lui et al., ). Alcohol consumption increases the risk of preterm birth and infants born small for their gestational age (Nykjaer et al., ).…”
Section: Alcohol Use In Pregnancymentioning
confidence: 99%